PAGUDEM: Upaya pemberdayaan komunitas dalam penanganan Diabetes Melitus di Probolinggo - Nur Hamim; Nafolion Nur Rahmat (P3HKI - Universitas Muhammadiyah Parepare, 2020)
Community service activities in the Maron Community Health Center Work Area, Probolinggo Regency, were carried out using an educational model approach and the formation of an Association for Diabetes Mellitus Sufferers (PAGUDEM). This activity aims to provide a better understanding to Diabetes Mellitus sufferers and the general public about how to overcome problems related to Diabetes Mellitus, carry out early detection, and control disability and the increase in Diabetes Mellitus sufferers. The findings of this activity are consistent with previous research which shows the effectiveness of the community model approach and diabetes education in preventing disability due to diabetes mellitus. Apart from that, this activity also has a positive impact on health, social, economic, as well as cultural and environmental aspects. Changes in people's attitudes and behavior regarding Diabetes Mellitus are also visible, where they become more aware of the importance of preventing and managing this disease, and are more proactive in maintaining a healthy lifestyle. Thus, this service activity not only provides direct benefits for Diabetes Mellitus sufferers but has also brought positive changes in the way people think and act regarding this condition.